A comparison of understanding Islamic debt concept among academic and administrative staff at Universiti Teknologi Mara (UiTM), Malaysia - Jusoh, Mohd Kamal Azman; Awang, Mohd Daud; Abdullah, Atikullah (2012)
Based on report, in 2009 total of 1,086 public servants had been declared bankrupt by the Insolvency Department. The majority of 72.74% are male employees, while only 27.26% are female employees. The existence of bankruptcy cases not only has tarnished the image of the public sector, but it also greatly affects the individuals involved. The bankrupt employees will lose their pension benefit when they are retired. This phenomenon is very shocking as the concept of Islamic debt has been discussed thoroughly in Islamic jurisprudence. It is the main foundation and guidance to the Muslim debtor and creditor. With that a study should be conducted to identify the level of understanding of the public servant regarding the concept and ethics of debt prescribed in Islam. This paper will discuss the comparative understanding of academic and administrative government servants who are Muslims in UiTM regarding the debt concept in Islam. Data in this paper is obtained from the questionnaire involving 690 respondents in UiTM Shah Alam, Pahang and Penang. Data is analyzed using the Statistical Package for Social Science (SPSS) version 19. The results have shown that the level of understanding academic employees is higher with mean score of 3.80 compared to administrative with 3.59 score at a moderate level. T-test results also show a significant relationship between the concept of lslamic debt understanding with group position.